Pengaruh Pendidikan Kewirausahaan Terhadap Niat Berwirausaha Mahasiswa - Yasin, Nurfatwa Andriani; Ahmad, Tri Sulkarnain (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
This study aims to determine the effect of entrepreneurship education on students of the Faculty of Economics, Pejuang University of the Republic of Indonesia. This study found that there was a positive and significant effect between entrepreneurship education on entrepreneurial intentions in students. With the formulation of the linear equation Y = 2.272 + 0.483 X1.R square is 0.197 which means that the students' intention to become entrepreneurs is influenced by entrepreneurship education by 19.7%. This study concludes that entrepreneurship education is able to convey the required knowledge and provide skills that are able to change students' intentions to become entrepreneurs into entrepreneurial activities. Although entrepreneurship education is not an absolute thing that leads to entrepreneurial intentions, this entrepreneurship education has its own way of motivating students to start entrepreneurial businesses.